2014
DOI: 10.1016/j.clcc.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Ganetespib, a Novel Hsp90 Inhibitor in Patients With KRAS Mutated and Wild Type, Refractory Metastatic Colorectal Cancer

Abstract: Seventeen patients with refractory KRAS mutated and wild type metastatic colorectal adenocarcinoma received single agent ganetespib in a single institution phase II study. The drug was well tolerated but did not yield any responses, although two patients achieved durable stable disease. Background Heat shock protein 90 (Hsp90) is a cellular chaperone that is required for the maturation and stability of a variety of proteins that play key roles in colon cancer initiation and progression. The primary objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 27 publications
2
29
0
Order By: Relevance
“…Details of eligible trials with an Hsp90 inhibitor were noted in Table II. The majority of Hsp90 inhibitors were tested in trials of monotherapy: 17-AAG (13,19,20,23), ganetespib (15,24,25), IPI-504 (21,26) and BIIB021 (27). There were also trials of combination of Hsp90 inhibitors, 17-AAG (14,17,18)/IPI-504 (16), with other anticancer drugs, including cytotoxic and molecularly targeted agents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of eligible trials with an Hsp90 inhibitor were noted in Table II. The majority of Hsp90 inhibitors were tested in trials of monotherapy: 17-AAG (13,19,20,23), ganetespib (15,24,25), IPI-504 (21,26) and BIIB021 (27). There were also trials of combination of Hsp90 inhibitors, 17-AAG (14,17,18)/IPI-504 (16), with other anticancer drugs, including cytotoxic and molecularly targeted agents.…”
Section: Resultsmentioning
confidence: 99%
“…The number of patients in these trials ranged between 11 and 99, with the median age between 51 and 68 years. A total of 10 types of cancer were described in these 15 trials, including breast cancer (13)(14)(15)(16), ovarian carcinoma (17), peritoneal carcinoma (17), multiple myeloma (18), renal cell cancer (19), prostate cancer (20,21), melanoma (22,23), colorectal cancer (24), lung cancer (25,26) and gastrointestinal stromal tumor (GIST) (27). The majority of patients had received prior therapies and had metastatic or recurrent diseases at baseline.…”
Section: Resultsmentioning
confidence: 99%
“…II trial reported in colorectal cancer, single-agent treatment with ganetespib demonstrated good tolerance but low efficacy in chemotherapy-refractory metastatic disease, independent of KRAS mutation status (42). Higher antitumor activity was seen in early clinical trials exploring combinations of HSP90 inhibitors with chemotherapies, including fluoropyrimidines (5-FU and capecitabine; ref.…”
Section: Discussionmentioning
confidence: 99%
“…S13). Previous studies have suggested that HSP90 inhibition may sensitize colorectal cancer cell lines to chemotherapy, and although monotherapy with HSP90 inhibitors has shown low efficacy in metastatic colorectal cancer (42), response has been obtained by combination therapy with HSP90 inhibitors and capecitabine (5-FU pro-drug) in patients who have progressed on fluoropyrimidines (43). Accordingly, to analyze a potential effect of HSP90 inhibition in vivo, we selected a CMS4 PDX model (MSS, KRAS/NRAS wild type, BRAF V600E mutated) for treatment in a randomized and controlled set-up.…”
Section: Hsp90 Inhibition May Alleviate Chemoresistance In Cms4 In Vivomentioning
confidence: 99%
“…Notably, the potential carcinogenic role of HSP-90 in activation of various oncogenic proteins and growth factors is currently of intense interest, particularly in colorectal cancer, which is why specific HSP90 inhibitors are currently being investigated as potential anticancer drugs (36). More importantly, HSP90 dependence acquired resistance to 5-FU therapy, as well as its potential role as a proangiogenic factor for the induction of VEGF and iNOS for de novo angiogenesis has been reported recently (2).…”
Section: Discussionmentioning
confidence: 99%